2016
DOI: 10.2967/jnumed.115.169763
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prostate Cancer with PET/MRI

Abstract: In the ongoing effort to understand and cure prostate cancer, imaging modalities are constantly evolving to assist in clinical decisions. Multiparametric MRI can be used to direct prostate biopsies, improve diagnostic yield, and help clinicians make more accurate decisions. PET is superior in providing biologic information about the cancer and is sensitive and highly specific. Integrated PET/MRI is a welcome technical advance with great potential to influence the diagnosis and management of prostate cancer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…Given the ordinal scale of PIRADS classification and Likert scale, calculating diagnostic accuracy using ROC analysis might be more adequate than doing it using fourfold tables. The improved diagnostic accuracy of PET/MRI and PET underlines the potential of integrated PET/MRI to further improve PCa diagnostics and is also mirrored in the present literature regarding integrated PET/MRI in primary PCa [3,19,26,27]. In particular, a recently published study from Eiber et al [19] reported of a significantly improved detection of PCa lesions and improved diagnostic accuracy as well as a reduced rate of uncertain lesions by using 68 Ga-PSMA PET and PET/MRI when compared to sole mpMRI.…”
Section: Discussionmentioning
confidence: 64%
“…Given the ordinal scale of PIRADS classification and Likert scale, calculating diagnostic accuracy using ROC analysis might be more adequate than doing it using fourfold tables. The improved diagnostic accuracy of PET/MRI and PET underlines the potential of integrated PET/MRI to further improve PCa diagnostics and is also mirrored in the present literature regarding integrated PET/MRI in primary PCa [3,19,26,27]. In particular, a recently published study from Eiber et al [19] reported of a significantly improved detection of PCa lesions and improved diagnostic accuracy as well as a reduced rate of uncertain lesions by using 68 Ga-PSMA PET and PET/MRI when compared to sole mpMRI.…”
Section: Discussionmentioning
confidence: 64%
“…Newly developed tracers exhibit increased accuracy for the detection of small, incipient metastatic foci [28][29]. Improvements in MRI techniques, and particularly in functional imaging, have enabled radiologists to play an important role in the risk stratification and management of patients [30][31][32]. 18 F-FDG PET/CT is primarily useful in the diagnosis and staging of prostate cancer because it combines the metabolic information of PET with the anatomic information of CT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the combination of the imaging techniques versus choline PET/CT alone achieved a significantly higher detection rate for LR. It is worth highlighting the increasing clinical and diagnostic role of the integrated PET/MRI scanner, an advanced technique that combines the anatomical and functional information provided by MRI with the higher specificity of PET [17]. This hybrid PET-MRI system has shown promising results in terms of tumor detection compared to MRI or PET alone [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth highlighting the increasing clinical and diagnostic role of the integrated PET/MRI scanner, an advanced technique that combines the anatomical and functional information provided by MRI with the higher specificity of PET [17]. This hybrid PET-MRI system has shown promising results in terms of tumor detection compared to MRI or PET alone [17]. For this reason, the high detection rate for MRI and choline PET/CT allows us to define the site of recurrence, assess for metastatic disease, and personalize salvage therapy.…”
Section: Discussionmentioning
confidence: 99%